Immunostimulant Effects of Bitter Leaves (Gymnanthemum amygdalinum (Del.) Sch.Bip.ex Walp.) Leaf Extract - Setiani, Lusi Agus; Wiendarlina, Ike Yulia; Rizkyani, Nanda Asyura; Fazri, Syifa Ainun (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2024)
In Indonesia, the widespread impact of COVID-19 has led to an increased interest in exploring natural immunostimulants as complementary therapies. One promising candidate is Gymnanthemum amygdalinum, commonly known as bitter leaf. Bitter leaf is a medicinal plant that can be used as an immunostimulant because it contains flavonoid compounds. This study aims to investigate the immunostimulatory effects of Bitter leaf extract obtained using the MAE method, particularly in enhancing immune function and the effective dosage in rats. The ethanolic extract of bitter leaf was made using the microwave-assisted extraction (MAE) method, which can potentially extract high levels of flavonoid compounds compared to other extraction methods in vivo. There were as many as 25 rats, which were divided into five treatment groups: the negative control was treated with CMC Na 0,5% (w/v); the positive control was treated with 4,5 mg/200 g body weight (BW) of Echinacea purpurea. The treatment groups from Dose 1; Dose 2; and Dose 3 were treated with an ethanol extract of bitter leaf at 14 mg/200 g BW, 28 mg/200 g BW, and 56 mg/200 g BW. Immunostimulant effect testing was carried out using the carbon clearance method, and the number of leukocytes was counted. In carbon clearance testing, each group was given a carbon solution intravenously; blood was taken at 5, 10, and 15 minutes via the tail vein, and its absorbance was measured using UV-Vis 675 nm. The count of leukocytes was observed using the chamber of a hemocytometer through a microscope. The research results showed that administration of doses I, II, and III provided an immunostimulant effect. Based on the results, the ethanolic extract from a bitter leaf from Dose III (56 mg/200 g BW) provided a stronger immunostimulant effect in rats based on the phagocytosis index parameters of (9.005) and the number of leukocytes of (8,370/µL).